LiquidReactionCell – a versatile setup for in situ synchrotron studies of compounds in liquid suspension and solution. Issue 5 (5th January 2023) - Jeppesen, Henrik S.; Nielsen, Ida G.; Kondrup, Jens Christian; Just, Justus; Lock, Nina
Abstract : A simple and versatile setup for in situ XAS and total scattering was developed and tested on Bi24 O31 X10 (X = Cl, Br). Abstract : There is an increasing interest in understanding the atomic level formation of functional materials, e.g. through nucleation and growth from their precursors in solution or through chemically induced phase transitions. Such information is achievable though synchrotron-based in situ X-ray absorption spectroscopy (XAS) and total scattering (TS) experiments. In this study we present a new and versatile setup for in situ investigations of chemical reactions. Our setup, LiquidReactionCell (LRC), is constructed in borosilicate glass, i.e., it is chemically inert and transparent to visible light, and it resembles regular laboratory glassware. The setup is designed to handle homogenous solutions and fine powder suspensions at ambient conditions, and it can be used to follow chemically or light induced reactions, for example. Chemical precursors can be added during data collection, and inert conditions can be obtained in the cell. Herein, we demonstrate the versatility and use of the LRC in XAS and TS experiments. Specifically, we compare data collected on powder suspensions in the LRC with data measured on powders under ideal conditions. Bi24 O31 X10 (X = Cl, Br) are emerging materials for photocatalysis and are used as model compounds herein. Gratifyingly, only minor differences are observed between data collected on suspensions in the LRC and data collected on a pressed pellet (for XAS) or on a powder in a Kapton capillary (for TS). These results propose that the LRC has the potential to cover a broad range of chemical reactions.